Prevalence of canine impaction among Kurdish people in Kurdistan region of Iraq. - Anees Mahmood Mudhir; Omar Fawzi Chawshli; Liqaa Jabur Hassan (Erbil Dental Journal, 2022)
Background and Objective: The permanent canine is the second most frequently impacted tooth following the third molars. The etiology of the impacted canine is ambiguous, but also multifactorial. There are some evidences that patients with a few certain features of occlusion may be at higher risk to the development of impacted canine. This study aimed to determine the prevalence of impacted maxillary and mandibular canine teeth in dental patient’s sub-population in the Kurdistan region of Iraq. Methods: This study comprised data from 2520 patients who attended the oral diagnosis and radiology clinic in specialized centers of dentistry in Duhok, Erbil and Slemany cities in a period between January 2015 to December 2019 were examined for the study. The age of the patients ranged from 15years to 45 years. Patients were examined in order to detect the impacted maxillary canines by intraoral examination, and OPG radiographs. Results: A total of 2520 patients, 152cases (6%) had impacted canines in upper and lower arches (49 males and 103 females) there was high significant relation (P <0.001) of impacted canine prevalence and the dental arches; higher prevalence was in the maxilla than inthe mandible (5.5% versus 0.5% respectively).